2008
DOI: 10.1007/bf03179459
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofCamellia sinensis L. whole plant extract on piglet intestinal ecosystem

Abstract: -The employment of Camellia sinensis L. whole plant extract as food supplement in livestock nutrition has been suggested in order to prevent usual livestock intestinal diseases. The aim of the present research was to test the effects of such plant extract on the composition of pig faecal microbiota. Preliminary in vitro fermentation trials evidenced in mixed pig faecal cultures, supplemented with the tested extract, an increase of total anaerobe (p = 0.02) and aerobe (p = 0.03) bacteria, and a decrease of clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“… a Assessment = conclusion of a reference on a hypothesized effect; b reference = trial x plant species x indication; c particularly unspecified or infectious diarrhea and gastrointestinal spasms + = reference proves evidently the hypothesized effect; ? = reference shows uncertain hypothesized effect; o = reference does not prove evidently the hypothesized effect 1 [ 147 , 148 ] 2 [ 149 – 152 ] 3 [ 153 ] 4 [ 154 ] 5 [ 69 76 , 155 – 158 ] 6 [ 69 ] 7 [ 63 , 66 ] 8 [ 159 ] 9 [ 62 , 160 ] 10 [ 63 , 64 ] 11 [ 66 ] 12 [ 77 ] 13 [ 161 , 162 ] 14 [ 163 , 164 ] 15 [ 165 – 170 ] 16 [ 170 ] 17 [ 171 ] 18 [ 172 ] 19 [ 124 , 125 ] 20 [ 124 , 173 ] 21 [ 174 – 176 ] 22 [ 177 ] 23 [ 178 ] 24 [ 179 ] 25 [ 175 , 176 , 180 – 183 ] 26 [ 184 ] 27 [ 185 ] 28 [ 181 ] 29 [ 186 ] 30 [ ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… a Assessment = conclusion of a reference on a hypothesized effect; b reference = trial x plant species x indication; c particularly unspecified or infectious diarrhea and gastrointestinal spasms + = reference proves evidently the hypothesized effect; ? = reference shows uncertain hypothesized effect; o = reference does not prove evidently the hypothesized effect 1 [ 147 , 148 ] 2 [ 149 – 152 ] 3 [ 153 ] 4 [ 154 ] 5 [ 69 76 , 155 – 158 ] 6 [ 69 ] 7 [ 63 , 66 ] 8 [ 159 ] 9 [ 62 , 160 ] 10 [ 63 , 64 ] 11 [ 66 ] 12 [ 77 ] 13 [ 161 , 162 ] 14 [ 163 , 164 ] 15 [ 165 – 170 ] 16 [ 170 ] 17 [ 171 ] 18 [ 172 ] 19 [ 124 , 125 ] 20 [ 124 , 173 ] 21 [ 174 – 176 ] 22 [ 177 ] 23 [ 178 ] 24 [ 179 ] 25 [ 175 , 176 , 180 – 183 ] 26 [ 184 ] 27 [ 185 ] 28 [ 181 ] 29 [ 186 ] 30 [ ...…”
Section: Resultsmentioning
confidence: 99%
“…Some clinical studies reported beneficial effects of Camellia sinensis (L.) KUNTZE on gut health as indicated by a reduced prevalence of postweaning diarrhea in piglets, but also a decrease in growth performance [ 124 ]. An experimental trial on a diet with Camellia sinensis (L.) KUNTZE whole plant extract revealed a significant decrease of Clostridia counts, but also of Enterococci counts in the feces of piglets compared to a standard diet with antibiotics [ 125 ]. Two in vivo studies showed also anti-influenza virus activity in mice [ 126 ] and chicken [ 127 ], which might be due to an inhibition of virus adsorption [ 126 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are extensively used in feed as growth promoters and health protectants (Hashemi and Davoodi, 2011; Abreu et al, 2012), particularly in Asian, African, and South American countries, and are gradually used in developed countries in recent years. In pig production, it is thought that oregano, cinnamon, Mexican pepper, thyme, oregano, and Camellia sinensis can decrease pathogenic microbial mass in the intestines (Manzanilla et al, 2004; Namkung et al, 2004; Zanchi et al, 2008); sangrovit, aged garlic extract, and allicin are able to increase body weight gain (Borovan, 2004; Tatara et al, 2008); thyme, clove, oregano, eugenol, and carvacrol are capable of improving pig performance (Oetting et al, 2006; Costa et al, 2007). Effects of phytogenic feed additives on the production performance of poultry are also reported (Hashemi and Davoodi, 2010).…”
Section: Plant Extractsmentioning
confidence: 99%
“…This is due to the influence of many factors such as climate, season, harvesting method and others (Borovan, 2004). Probably for this reason there is a multiplicity of controversial results Specific blend of herbal extract increase ADG, decrease feed conversion ratio in finishing pigs Liu et al (2008) Aged garlic extract, allicin improved body weight, morphological properties of intestine villi and non-specific defense mechanisms of piglets Tatara et al (2008) Camellia sinensis decrease of clostridia and enterococci counts in the faeces of piglets Zanchi et al (2008) obtained in different scientific studies examining the effect of these substances in animal nutrition. Accordingly, it is necessary to select effective plant extracts, standardize them and investigate a potential synergistic benefit deriving from their combination (Budzinski et al, 2000;.…”
Section: Plant Extractsmentioning
confidence: 99%